Inhibition of lymphocyte mediated cytotoxicity by perforin antisense oligonucleotides. - Acha-Orbea, H (1990)
The granule/perforin exocytosis model of CTL mediated cytolysis proposes that CTL, upon recognition of the specific targets, release the cytolytic, pore-forming protein perforin into the intercellular space which then mediates the cytotoxic effect. However, direct evidence for the involvement of perforin is still lacking, and indeed, recent results even seem incompatible with the model. To determine directly the role of perforin in CTL cytotoxicity, perforin antisense oligonucleotides were exogenously added during the stimulation of mouse spleen derived T cells and human peripheral blood lymphocytes (PBL), respectively. Perforin protein expression in lymphocytes was reduced by up to 65%, and cytotoxicity of stimulated T cells by as much as 69% (5.7-fold). These results provide the first experimental evidence for a crucial role of perforin in lymphocyte mediated cytotoxicity.